Pengaruh Kreativitas dan Motivasi Berwirausaha terhadap Minat Berwirausaha Mahasiswa Pendidikan Ekonomi di Universitas Pendidikan Ganesha - Pengastuti, Ni Komang Feby Ayu; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This research was conducted to test: (1) the influence of creativity on student entrepreneurship interests, (2) the influence of entrepreneurial motivation on student entrepreneurship interests, and (3) the influence of creativity and entrepreneurial motivation on the entrepreneurial interests of economic education students at Ganesha University of Education. This type of research is causal research. The population in this study is students of the Economic Education study program for the 2018 to 2021 school years, which amounts to 277 students. The sample technique used is a simple random sampling technique. The method of data collection in this study is to use questionnaires and documentation with data analysis methods, namely multiple linear regression analysis. Hypothesis test using t-test and F-test processed with the help of IBM SPSS 25.00. The results of this study show that (1) there is an influence between creativity and entrepreneurial interests, partially with a signification value of 0.000<0.05, (2) there is an influence between entrepreneurial motivation and student interests, partially with a signification value of 0.000<0.05, and (3) there is an influence of creativity and entrepreneurial motivation on the entrepreneurial interests of students of Economic Education at Universitas Pendidikan Ganesha simultaneously with a signification value of 0.000<0.05.